2014
DOI: 10.1074/jbc.m114.611970
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein H Suppresses Cellular Senescence through Genome Maintenance and Redox Regulation

Abstract: Background: Selenoprotein H (SelH), a proposed redox-responsive DNA-binding protein, is little-studied. Results: SelH shRNA cells display severe proliferation defects and accelerated senescence with abnormal responses to DNA damage and oxidative stress. Conclusion: SelH suppresses senescence and may have important roles in gatekeeping genomic integrity. Significance: Learning how SelH keeps senescence in check is crucial for advancing our understanding linking selenium and aging intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 79 publications
2
23
0
Order By: Relevance
“…Thus, SelH appears to be a sensor of oxidative stress in nucleus, where it may play a dual role in redox maintenance as an antioxidant and regulation of gene expression as a transactivator. Such diverse dealings of SelH in genome maintenance and redox regulation is consistent with our recent functional analyses demonstrating a role of this selenoprotein in the protection against replicative senescence in a manner depending on ATM, p53, and reactive oxygen species .…”
Section: Nuclear Selenoproteins and Functionssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, SelH appears to be a sensor of oxidative stress in nucleus, where it may play a dual role in redox maintenance as an antioxidant and regulation of gene expression as a transactivator. Such diverse dealings of SelH in genome maintenance and redox regulation is consistent with our recent functional analyses demonstrating a role of this selenoprotein in the protection against replicative senescence in a manner depending on ATM, p53, and reactive oxygen species .…”
Section: Nuclear Selenoproteins and Functionssupporting
confidence: 90%
“…In mammals, SelH mRNA expression is high during embryogenesis, in certain tissues such as brain, thymus, testes and uterus in mice, and in some human cancerous cells such as colorectal HCT116 and prostate LNCaP cells . The expression of SelH mRNA can be upregulated after binding of metal transcription factor‐1 to its metal response element and upon cellular exposure to H 2 O 2 . Thus, SelH appears to be a sensor of oxidative stress in nucleus, where it may play a dual role in redox maintenance as an antioxidant and regulation of gene expression as a transactivator.…”
Section: Nuclear Selenoproteins and Functionsmentioning
confidence: 99%
“…This may explain why current models of dietary Se or selenoprotein deficiency in mice do not recapitulate normal aging sufficiently or comprehensively. Although Gpx1 −/− mice do not show aging phenotypes up to 20 months of age (Ho et al ., ), primary Gpx1 −/− embryonic fibroblasts (de Haan et al ., ) and selenoprotein H knockdown MRC‐5 cells (Wu et al ., ) show senescence‐like features in a ROS‐dependent manner. Furthermore, heterozygous mutations in SECISBP2 , a gene encoding SBP2 essential for the expression of all selenoproteins, lead to shortened telomeres in humans (Schoenmakers et al ., ), and such effect appears to be independent of telomerase (Squires et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, knockdown of SEPH expression renders cancer cells susceptible to H 2 O 2 (32). Recent work by Wu et al (47) showed that SEPH knockdown causes oxidative stress, which inhibits proliferation and induces senescence in fibroblasts. In that study, the authors found that H 2 O 2 exposure in SEPH-deficient cells provoked a sustained DNA damage response and senescence, which was inhibited by loss of ATM or p53 function.…”
Section: Discussionmentioning
confidence: 99%